Long-Term Use of Riluzole Could Improve the Prognosis of Sporadic Amyotrophic Lateral Sclerosis Patients: A Real-World Cohort Study in China - Chen, Lu; Liu, Xiaolu; Tang, Lu; Zhang, Nan; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2016)
Objectives: To investigate the effectiveness of riluzole in a long-term follow-up of cohort with sporadic amyotrophic lateral sclerosis (ALS) in a real-world study. Methods: Patients with ALS between 2007 and 2013 were followed up every 3 months. Survival and tracheotomy were predefined as primary outcome measures. The cumulative defined daily dose (cDDD) of riluzole was estimated. The patients in the riluzole group were classified into 1 of 3 subgroups according to the cDDD quartiles. Survival was analyzed using Kaplan–Meier and Cox regression analysis. Results: Of the 1,540 ALS patients, 415 (26.9%) used riluzole, and the remainder did not. In the riluzole group, the age at onset was greater (p = 0.016), the diagnostic delay was shorter (p < 0.0005), the body mass index (BMI) was higher (p < 0.0005), and the scores for both the functional rating scale (FRS) and the revised FRS (FRS-R) were higher (both p < 0.0005) than those of the control group. The median cDDD of riluzole was 28 (2,800 mg). Although Kaplan–Meier analysis did not reveal a significant difference between the two groups (p = 0.780), it showed that the prognosis of the beyond quartile 3 subgroup [cDDD ≥ 168 (16,800 mg)] was significantly better than that of the other groups [adjusted HR 0.488 (0.320–0.746), p = 0.001]. Conclusion: In China, older ALS patients and patients who had a higher BMI, shorter diagnostic delay, and higher FRS or FRS-R scores were more likely to use riluzole. Long-term use of riluzole was associated with a better prognosis for ALS patients, whereas short-term use had little effect on survival.